Evaluating the Effectiveness of Marketing Strategies on Customer Visit Intentions: Evidence from Local Restaurants in Boac, Marinduque (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the comparative effectiveness of social media marketing and traditional marketing in influencing customer visit intention to local restaurants in Boac, Marinduque, Philippines, a provincial and community-based market context that remains underrepresented in marketing research. Guided by the Theory of Planned Behavior, Integrated Marketing Communication (IMC) framework, and the DINESERV model, the study adopts a quantitative, descriptive–comparative research design involving 200 restaurant customers selected through convenience sampling.Findings reveal that social media marketing particularly social networking platforms (Facebook, Instagram, TikTok) and electronic media campaigns is significantly more effective than traditional marketing in shaping customer visit intention across four key dimensions: food quality, price perception, service quality, and restaurant atmosphere. Visual content, responsiveness, and real-time engagement emerged as dominant drivers of customer perception and behavioral intention. In contrast, traditional marketing strategies such as print advertisements, promotional handouts, and public relations were found to be only moderately effective, with word-of-mouth remaining the most influential traditional channel.Inferential analysis indicates that gender and employment status significantly moderate perceptions of marketing effectiveness, while age and income level do not exert a statistically significant influence. These results suggest that digital marketing strategies in provincial settings demonstrate broad demographic reach, reinforcing their strategic value for small and medium enterprises (SMEs).The study contributes empirically by extending marketing effectiveness research to a localized, non-metropolitan context, offering actionable insights for restaurant owners and policymakers. Practically, the findings support the adoption of hybrid marketing strategies that integrate digital visibility with community-based engagement. The study aligns with Sustainable Development Goal (SDG) 8 (Decent Work and Economic Growth) by strengthening local enterprise competitiveness, SDG 9 (Industry, Innovation, and Infrastructure) through digital adoption, and SDG 11 (Sustainable Cities and Communities) by supporting resilient local food systems.Overall, the study underscores that strategic social media marketing is a critical lever for sustainable business growth, customer engagement, and inclusive economic development in provincial economies.